Comparatif Analysis Of Production Input In Use Granola and Cipanas Potato Farming On Production In Kayu Aro Barat District Kerinci Regency - Nainggolan, Saidin; Damayanti, Yusma; Saragih, Rachel (JALOW | Journal of Agribusiness and Local Wisdom, 2026)
This study aims to (1) analyze the general picture of granola potato farming compared to Cipanas potato farming in Kayu Aro Barat District, Kerinci Regency, and (2) analyze the comparison of production inputs between granola potato farming and Cipanas potato farming on production. The analysis used multiple linear regression with a slope dummy. The study was conducted in Kebun Baru, Gunung Labu, and Giri Mulyo Villages. The results show that potato farming activities begin with land preparation, seed planting, fertilization, pest control, and harvesting. Production inputs that significantly affect production are land area, seeds, organic fertilizer, SP 36, and urea. Seeds and medicines are more responsive to granola, while land area, fertilizer, and labor are more responsive to Cipanas. The granola variety produces significantly higher production than Cipanas